MANAJEMEN USAHA SALON KECANTIKAN DI KECAMATAN PADANG TIMUR - Rianda, Metsy; Rostamailis, Rostamailis; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
The background of this research was motivated by the rapid emergence ofcompetition in the world of beauty salons make a beauty salon business must payattention to the implementation of management functions in order to get ahead inbusiness. This study aims to reveal the beauty salon business management applicationbased on the elements in the management of Planning, Organizing, Actuating, andControlling in a beauty parlor in East Padang District. This research was conductedby quantitative descriptive approach. The study population is all employees andbusiness leaders in the beauty salon East Padang District totaling 55 people. Samplesare entire populations sampled or with total sampling technique. Data analysis wasperformed using the percentage of respondents' level of achievement and thefrequency distribution of research data. Data retrieved through a questionnaire(questionnaire) by using a Likert scale which first tested through the analysis phasevalidity and reliability. The results showed that the percentage of respondent’sattainment Beauty Salon Business Management on indicators of planning is 63% withpoor category, organizing indicators was 56% with poor category, actuatingindicators was 52% with a very poor category, and controlling indicators was 55%with bad category. Based on the research results suggested a beauty parlor reallyimplement management functions in executing its business so that business successcan be achieved.Key word: Beauty Salon Business Management